A prosecutor's "ideal" sexual assault case: a mixed-method approach to understanding sexual assault case processing - Ropp, John W. (Criminology, 2024)
Research continues to explore factors that contribute to high rates of attrition among sexual assault cases. Comparatively little is known, however, about prosecutorial, as opposed to police, decision-making in these cases. Using a mixed-method approach to analyze (1) 175 case files from a midsize policing agency in the West with trained sexual assault investigators and (2) detailed prosecutor notes from 52 corresponding cases, we explore patterns in three key outcomes: (a) arrest, (b) referral for prosecution, and (c) charging. Logistic regression results indicate that fewer variables predicted case outcomes compared with previous studies, suggesting that specially trained officers may be more adept at dismissing "rape myth" factors. Qualitative analysis of prosecutorial case notes, however, revealed that prosecutors tended to compare specific case elements to an envisioned "ideal" case, which frequently aligned with some pervasive rape myths prevalent in society. Prosecutors focused heavily on convictability, anticipating how a potential jury would respond to the case. Although specially trained investigators may better disregard extralegal rape-myth factors, these myths still plague decision-making at the prosecutorial stage indirectly via concerns for juror interpretation of the facts. We find strong support for the "downstream" perspective of prosecutorial decision-making.